The Osteoarticular Infection in a Pediatric Emergency Setting: A Challenging Diagnosis. Issue 2 (February 2020) - Boccuzzi, Elena; Buonsenso, Danilo; Ferro, Valentina; Raucci, Umberto; Reale, Antonino; Piga, Simone; Deriu, Daniele; Krzysztofiak, Andrzej
Abstract : Objectives: The study aimed to evaluate the emergency department (ED) presentation of children with a diagnosis of osteomyelitis, septic arthritis, or both. Methods: A retrospective single-center study was conducted on all children aged between 1 month and 18 years evaluated in the ED over a 7-year period and having a final diagnosis of osteoarticular infection. One hundred seventeen patients were enrolled. Results: Only 39.3% of patients were admitted after the first evaluation, and only 45.3% had a proper diagnosis of admission. Pain was the only symptom reported by all. White cell count, C-reactive protein level, and erythrocytes sedimentation rate were normal in 49.5%, 21.4%, and 17.1% of children, respectively. X-ray findings were unremarkable in 48% of cases. Clinical and bone structural sequelae were described in 19.23% and 56.86% of all cases. No statistically significant differences were found among osteomyelitis, arthritis, and the combination of both regarding all considered variables, except for structural outcomes resulting more significant in the third group. Significant differences were evident in clinical manifestations, blood examinations, and findings of osteolysis between patients diagnosed within and after 1 week since the disease onset. Finally, questionable differences between white blood cells and C-reactive protein level were found among patients younger than 5 years and older ones, whereas a history of trauma was more often reported in the second group. Conclusions: The difficulty in recognizing osteoarticular infection in a pediatric ED can be due to the possible lack of the classic signs and symptoms, and the absence of specific laboratory and radiologic findings.